2021
DOI: 10.1177/0002716221995158
|View full text |Cite
|
Sign up to set email alerts
|

How to Address Homelessness: Reflections from Research

Abstract: This commentary considers policy implications of research in this volume and elsewhere, and we emphasize the benefits of policy approaches that move “upstream,” to the prevention of homelessness. Policies that address the structural causes of homelessness, described by numerous articles in this ANNALS volume, are the furthest upstream and may be the most important in eradicating homelessness, and policies aimed at prevention are next. We point out that effective prevention requires targeting those most at risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Research has demonstrated that mental health and substance use services, while important, do not affect the stability of housing outcomes for individuals experiencing homelessness (O'Regan, 2021). Thus, immediate and low-barrier housing should be prioritized (O'Regan, 2021). In a randomized controlled trial of a Housing First intervention for adults with mental disorders in Toronto, it was found that the Housing First approach was strongly associated with rapid transitions to sustained housing: 70.4 percent of Housing First participants versus 27.9 percent of treatment-as-usual participants (Lachaud, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that mental health and substance use services, while important, do not affect the stability of housing outcomes for individuals experiencing homelessness (O'Regan, 2021). Thus, immediate and low-barrier housing should be prioritized (O'Regan, 2021). In a randomized controlled trial of a Housing First intervention for adults with mental disorders in Toronto, it was found that the Housing First approach was strongly associated with rapid transitions to sustained housing: 70.4 percent of Housing First participants versus 27.9 percent of treatment-as-usual participants (Lachaud, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness is often described as a “crisis”—including a water and toilet “crisis” in wealthy cities and countries of the Global North (Lee et al, 2021; Mitchell, 2020; O'Regan et al, 2021). In this article, we sought to interrogate this “crisis” narrative and shift focus to the dwelling paradox, a produced contradiction of advanced capitalist societies and a space of entrapment in which no home normally means no water.…”
Section: Discussionmentioning
confidence: 99%
“…Somerville (1992) criticizes the rudimentary definition of homelessness as lack of housing affordability, and expands the definition to include dimensions of privacy and shelter, along with several others, to define what home is and what subsequently will define the lack thereof or homelessness. O’Regan et al (2021) say that homelessness is a traumatic experience for individuals and families who face it as it disrupts their work, health, education, and relationships.…”
Section: Understanding Homelessnessmentioning
confidence: 99%